Swearing and cursing contexts and practices in a critical linguistic perspective - Nassenstein, Nico 1985-; Storch, Anne 1968- (Language and social life, 2020)
While most of the more recent influential work on swearing has concentrated on English and other languages from the Global North, looking at forms and functions of swear words, this contribution redirects the necessary focus onto a sociolinguistics of swearing that puts transgressive practices in non-Western languages into the focus. The transdisciplinary volume contains innovative case studies that address swearing and cursing in parts of the world characterized by consequences of colonialism and increasingly debated inequalities. Turning away from more conventional and established methodologies and theoretical approaches, the book envisages to address transgressive linguistic practices, performances and contexts in Africa, Asia, America and Europe –including individuals' creativity, subversive power and agency. Due to its interdisciplinary and non-mainstream focus, this volume is an essential addition to the field of studies